Municipal Capital Maintenance and Fiscal Distress - Bumgarner, Mary; Martinez-Vazquez, Jorge; Sjoquist, David L. (The Review of Economics and Statistics, 1991)
This paper formalizes and empirically tests the hypothesis that the deficient maintenance of public infrastructure is caused by fiscal distress. We utilize a production-decision framework in which public officials combine maintenance and new capital to produce a desired level of capital services. The behavior implied in the fiscal distress hypothesis is treated as perverse deviations from the optimal production path. The empirical findings from cross-sectional expenditures data give support to the fiscal distress hypothesis.